Additively manufactured dual-functional metamaterials with customisable mechanical and sound-absorbing properties - Li, Zhendong; Zhai, Wei; Li, Xinwei; Yu, Xiang; Guo, Zichao; Wang, Zhonggang (Virtual and physical prototyping, 2022)
Acoustic metamaterials with broadband sound-absorbing capacity open up applications in aerospace, automotive, marine, defense, etc. For such applications, sound-absorbing materials that can withstand complex loading conditions are essential. Hence, to address acoustic and mechanical requirements simultaneously, we propose plate-reinforced dual-functional micro-lattice metamaterials (PDMMs) that exhibit elastic isotropy, dual crushing stages with a specific energy absorption up to 25.82 kJ/kg, and ultra-broadband sound absorption from 0.97 kHz to 6.30 kHz. The remarkable elastic isotropy lies in the topology-induced structural stiffness homogenising effect. The transition from single to dual plateau anti-compression stages is controlled by tailoring the structural local strength. On-demand broadband sound absorption is achieved by modulating the parallel coupling and cascade resonance effects, and the physical mechanism is revealed by examining impedance matching and system damping states. Overall, the presented novel metamaterials exhibit exceptional application potentials by overcoming the trade-offs usually found in traditional mechanical and acoustic metamaterials.